The Influence of Ice-Breaking Application on the Mathematics Learning Motivation of Elementary School Students - Listiana Ayu Pratiwi; Iyan Rosita Dewi Nur (Jurnal Inovasi Matematika, 2022)
One of the efforts used so that students' motivation to learn mathematics can rise is by giving ice-breaking in learning mathematics. The purpose of this study was to determine the effect of ice-breaking on the mathematics learning motivation of elementary school students. This study uses a quantitative type with a pre-experimental research design. The research design used was One group Pretest-Posttest Design with a sample of 17 students of SD class V. Data collection techniques were carried out by giving learning motivation questionnaires before treatment (ice-breaking) and after treatment (ice-breaking). breaking). Data analysis consisted of descriptive statistical analysis and inferential statistics in the form of hypothesis testing using t-test. From the results of hypothesis testing using t-test, it is known that there is a difference in average motivation to learn before and after ice-breaking. The average motivation to learn after ice-breaking is higher than before ice-breaking. Thus it can be concluded that there is an effect of giving ice-breaking on learning motivation.